NCBI SARS-CoV-2 resources [electronic resource] - U.S. National Institutes of Health. National Library of Medicine.National Center for Biotechnology Information (Bethesda, MD National Library of Medicine, 2020)
COVID-19 is an emerging, rapidly evolving situation. Get the latest public health information from this site.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Open education; Open access publishing; Education, Higher; COVID-19 (Disease) -- Research -- Electronic information resources; COVID-19 (Disease) -- United States -- Electronic information resources; Open access publishing